High salt activates p97 to reduce host antiviral immunity by restricting Viperin induction. (15th November 2021) - Yuan, Yukang; Miao, Ying; Ren, Tengfei; Huang, Fan; Qian, Liping; Chen, Xiangjie; Zuo, Yibo; Zhang, Hong‐Guang; He, Jiuyi; Qiao, Caixia; Du, Qian; Wu, Qiuyu; et al.
Abstract: High‐salt diets have recently been implicated in hypertension, cardiovascular disease, and autoimmune disease. However, whether and how dietary salt affects host antiviral response remain elusive. Here, we report that high salt induces an instant reduction in host antiviral immunity, although this effect is compromised during a long‐term high‐salt diet. Further studies reveal that high salt stimulates the acetylation at Lys663 of p97, which promotes the recruitment of ubiquitinated proteins for proteasome‐dependent degradation. p97‐mediated degradation of the deubiquitinase USP33 results in a deficiency of Viperin protein expression during viral infection, which substantially attenuates host antiviral ability. Importantly, switching to a low‐salt diet during viral infection significantly enhances Viperin expression and improves host antiviral ability. These findings uncover dietary salt‐induced regulation of ubiquitinated cellular proteins and host antiviral immunity, and could offer insight into the daily consumption of salt‐containing diets during virus epidemics. Synopsis: High salt levels in the food promote the degradation of the Viperin deubiquitinase USP33, thus interfering with Viperin stability and weakening antiviral responses. A low‐salt diet enhances Viperin expression and promotes antiviral activity. High‐salt diet promotes p97 acetylation to recruit USP33 for degradation. USP33 downregulation reduces Viperin levels, thereby attenuating cellular antiviral potency. Low‐salt diet inhibits p97 activity and promotes Viperin expression, thus improving host antiviral ability. Abstract : High salt levels in the food promote the degradation of the Viperin deubiquitinase USP33, thus interfering with Viperin stability and weakening antiviral responses. A low‐salt diet enhances Viperin expression and promotes antiviral activity.